Diffuse Ectopic Deciduosis Imitating Peritoneal Carcinomatosis with Acute Abdomen Presentation: A Case Report and Literature Review - Pavel Sorokin; Andrei Nikiforchin; Aleksandr Panin; Aleksandr Zhukov; Vadim Gushchin; Mark Kurtser (Case Reports in Obstetrics and Gynecology)
During pregnancy, decidual tissue can occur beyond the endometrium, predominantly on the surface of the uterus, fallopian tubes, and ovaries. This condition, called ectopic deciduosis, generally is not accompanied by any symptoms and complications, does not require treatment, and resolves completely soon after labor. However, rarely it can present with acute abdomen syndrome or imitate peritoneal malignancy and, thus, cause diagnostic difficulties and unnecessary interventions. Here, we report a challenging case of a pregnant woman admitted with acute peritonitis caused by ectopic deciduosis that mimicked peritoneal carcinomatosis. This uncommon manifestation of deciduosis hindered correct diagnosis and led to excessive surgery. While the management of the patient presented is regrettable, the case highlights the natural history of deciduosis, and therefore, important lessons could be learned from it.